The Antarctic Treaty System: Politics, Law, and Diplomacy - Gomes, Diane (Columbia Journal of Environmental Law, 2020)
THE ANTARCTIC TREATY SYSTEM: POLITICS, LAW, AND DIPLOMACY. By Jeffrey D. Myhre. Westview Special Studies in International Relations. Boulder, Colo.: Westview Press, Inc., 1986. Pp. 162.